Compact Archimedean spiral antenna with high gain for electrostatic discharge detection - Tong Wang; Dongwei Chen; Mingjie Li; Weidong Liu; Qingyuan Fang (IET Microwaves, Antennas & Propagation, 2024)
Abstract A compact Archimedean spiral antenna with high gain for electrostatic discharge (ESD) detection is investigated. A frustum‐shaped cavity proposed in this work is formed to optimise the maximum antenna gain. Additionally, a helix arm is loaded to enhance antenna gain in lower band. The measured results demonstrate that the proposed antenna, which employs a unidirectional radiation mode, exhibits a maximum antenna gain ranging from −0.74 dBi to 9.46 dBi and a voltage standing wave ratio less than 3 across a frequency range of 0.65–5 GHz. A test system consisted of proposed antenna and a commercial ESD detection antenna is established. The verified results indicate that the proposed antenna has a performance close to the commercial antenna, so that proposed antenna with compact size is preferred to be utilised for ESD detection.